Reprint of: Service innovation in sustainable product service systems: Improving performance under linguistic preferences - Tseng, Ming Lang (Animo Repository, 2019)
Sustainable product service systems enable firms that are operating under resource limitations to deliver the best possible outcomes in terms of social well-being and economic growth. However, prior studies have not yet investigated the function of service innovation in sustainable product service systems or analyzed the convergence of importance and performance weighting in maximizing resource utilization in the supply chain. Moreover, prior studies have not yet integrated and proposed a complex interrelationship-driven hierarchical model including qualitative preferences or identifying weighting under linguistic preferences. This study applied the fuzzy Delphi method, fuzzy importance performance analysis and an analytical network process to analyze an interrelationship-driven hierarchical model of service innovation in sustainable product service systems. Hence, this study provides a set of attributes and a hybrid method to assess the model as well as linguistic preferences to weight the importance and performance measures. The results present four features that are included in the model: sustainable consumption, collaborative advantage, innovation activities and service innovation capabilities. Therefore, when building sustainable product service systems, firms should maintain operations and aim for business synergy in self-generated innovative products/services along with high-quality products/services, collaboration innovation and product and service innovations. Managerial and theoretical implications are discussed. © 2019 Elsevier B.V.